A Novel Blockchain based Software Defined Network (SDN) Architecture to Curb the Impact of DoS/DDoS - Sanyal, Subhasis; Barai, Mohit Kumar; Goplani, Anil (International Journal of Electrical, Electronics and Computers, 2021)
The proliferation of virtualization or containerization has created a new state of the art in the networking domain; Software Defined Networking (SDN). In the prior state of the art, networking was performed through two abstractions, a "Data plane" and a "Control plane." Whereas in SDN, it's done via a new centralized "Network OS" and a "Virtualization Layer." The "Network OS" runs on servers, observing and controlling the data plane of the "Virtualization Layer." Even though this architecture has given flexibility and agility to new network development and management, but it has created various security vulnerabilities like confidentiality, integrity, availability, etc. Here in this paper, a novel blockchain-based architecture has been proposed to unravel a particular issue, denial of services (DoS). In the proposed state of the art, a novel layered architecture has been considered. From the top, the control plane has been decomposed into a decentralized blockchain layer. A fog layer follows this. Blockchain-based multiple fog nodes or fog servers will be connected to numerous blockchain light nodes inside the fog layer. The user plane will be directly related to the fog layer. Also, here a particular type of intelligent node has been introduced. The proposed state-of-the-art shows more willingness and adaptability to surpass the challenges of vulnerabilities due to DoS and DDoS while maintaining scalability.